(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article proposes an analogy between the dance, gestures and writing of Hijikata Tatsumi – Japanese artist, creator of butoh between the 1950s and 1980s – and writing as approached by the French psychoanalyst Jacques Lacan, especially his notion of jouissance, linked to a specific approach of the notion of the body. To this end, we focused mainly on the way Hijikata created butoh, as well as on his notation system, called buto-fu, bringing him closer to psychoanalytic theory, notably to what Lacan approached, with Japanese calligraphy, as what we call jouissance writing. In this article, we deal with the concepts involved, making use of Lacanian metaphors and illustrations, such as the litoral, taking Hijikata as the guide and practical anchor for the theory that was configured as the object of the research.